Peran Bank Sampah: Efektivitas dalam Meningkatkan Pendapatan (Studi Kasus di Kota Bekasi) - Rifani, Rizka Aulia; Ningtias, Vera Monica; Nugroho, Sandi Dwi; Prasojo, Anggoro Adi; Azzahra, Syifa; Syafitri, Febriyana; Putri, Nachelda Aristawidya Eka; Ardiyansah, Ardiyansah (ANTASENA: Governance and Innovation Journal, 2025)
Waste has become a major problem in urban areas such as Bekasi City, where increasing waste volumes demand innovative and community-based management strategies. The Patriot Central Waste Bank (BSIP) serves as a sustainable solution that not only reduces waste but also provides economic benefits for the community. This study aims to evaluate the effectiveness of BSIP in improving household income and raising environmental awareness among residents. A blended research strategy was employed, combining quantitative methods via surveys of 91 respondents and qualitative approaches through in-depth interviews and direct observations. Data analysis was conducted using SPSS for validity and reliability testing, alongside descriptive analysis to understand BSIP’s role in supporting local livelihoods. The findings reveal that BSIP is capable of reducing approximately 80 tons of waste monthly and helping residents accumulate savings worth billions of rupiah. Additionally, BSIP organizes training programs in areas such as waste separation, creative recycling, and home waste management, equipping the public with income-generating skills. The success of this initiative is supported by multi-stakeholder collaboration, involving local government, the private sector, and grassroots communities. Future research should expand the scope of respondents and explore digital innovations that could enhance the efficiency and sustainability of waste bank operations in other regions